HumanizAS Project: Experience with students of the Degree in Medicine at the University of Valladolid (2019-2024) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2025)
The humanizAS project implements the "Interview with a Healthcare Professional" activity as a compulsory practice in the Degree in Medicine at the University of Valladolid. Integrated into the second-year Psychology course, it facilitates early clinical contact and humanization. This activity has been carried out for the last five academic years (2019-2024). The methodology requires collaborators with a minimum of five years of experience to obtain an extensive perspective on the clinician-patient relationship and the management of illness. Results show high satisfaction among participating students and professionals. The project, supported by ICOMVA and with a multidisciplinary focus, is validated as an innovative tool for introducing humanistic reflection into the initial training of future doctors.
Keywords: humanization, medical education, teaching innovation, interview, therapeutic alliance.